2005
DOI: 10.1161/01.str.0000170712.46106.2e
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 Facilitates Vascular Endothelial Growth Factor-Induced Angiogenesis in the Mature Mouse Brain

Abstract: Background and Purpose— A better understanding of angiogenic factors and their effects on cerebral angiogenesis is necessary for the development of effective therapeutic strategies for ischemic brain injury. Vascular endothelial growth factor (VEGF) has been shown to induce angiogenesis in the adult mouse brain. However, the function of angiopoietin-2 (Ang-2) in cerebral angiogenesis has not been clarified. The goal of this study was to identify the combined effects of VEGF and Ang-2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 29 publications
3
67
2
1
Order By: Relevance
“…Ang-2, a natural antagonist of Ang-1, destabilizes the established vasculature, allowing formation of new vessels to occur in the endothelium (Maisonpierre et al 1997;Yuan et al 2009). Also, Ang-2 promotes or inhibits angiogenesis in different micro-environments (Thurston et al 2000;Jones et al 2001;Lobov et al 2002;Zhu et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang-2, a natural antagonist of Ang-1, destabilizes the established vasculature, allowing formation of new vessels to occur in the endothelium (Maisonpierre et al 1997;Yuan et al 2009). Also, Ang-2 promotes or inhibits angiogenesis in different micro-environments (Thurston et al 2000;Jones et al 2001;Lobov et al 2002;Zhu et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Ang-2 competitively inhibits the Ang-1/ Tie-2 interaction, leading to disruption of blood vessels (Maisonpierre et al 1997;Asahara et al 1998). Furthermore, Ang-1 and Ang-2 protect the peripheral vasculature from leakage (Thurston et al 1999;Zhu et al 2005;Lee et al 2009), which may account for its anti-edema effects after cerebral ischemia.…”
mentioning
confidence: 99%
“…Vascular endothelial growth factor is known to limit the expression of such junction proteins. 17,37,38 In parallel to its permeability effect, we observed that VEGF decreases claudin5 and VE-cadherin expression in the ischemic cortices and this effect was abolished in the presence of Ang2. These effects are similar with those reported by Lee et al, 32 who showed that Ang1 counteracts the VEGF-induced increase in vascular permeability by upregulating tight junction protein zonula occludens-2.…”
Section: Discussionmentioning
confidence: 65%
“…[13][14][15] As an example, both pro-and antipermeability properties have been reported for Ang2 in peripheral tissues as a function of the specific microenvironments. [16][17][18] Furthermore, Ang2 has been described in the brain as an angioneurin, a neologism coined by Zacchigna et al 19 to encompass a particular class of molecules that affects both the vascular and the nervous systems. Paradoxically, although Ang2 is commonly described as an angiogenic factor, data reporting a role for this cytokine in the brain mostly relate to the nervous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…1А), а также увеличивает продукцию лактата по сравнению с контрольной серией экспериментов (контроль -12,01 нмоль/мкл, FM19G11 -48,38 нмоль/мкл). Увеличение экспрессии VEGF при подавлении активности HIF-1 соответствует данным о том, что в клетках астроглии экспрессия VEGF находится под частичным контролем этого транскрипционного фактора [18].…”
Section: результаты и обсуждениеunclassified